Microchips eletroforéticos de vidro com detecção condutométrica sem contato para análise de ânions inorgânicos em amostras reais - Freitas, Camilla Benevides (2014)
This work describes the evaluation of commercial microchip electrophoresis system for the analysis of inorganic ions in different real samples. The electrophoretic separation was carried out in commercial glass microchip with integrated capacitively coupled contactless conductivity detection (C4D). The optimization process was performed ranging the concentration background electrolyte as well as detection parameters, frequency and amplitude signal. Furthermore, analytical performance was evaluated with linearity, repeatability and recovery study. The best separation of chloride (Cl-), nitrate (NO3-), sulfate (SO42-) and nitrite (NO2-) was obtained with mixture of lactic acid (30 mmolL-1) and histidine (15 mmolL-1). Frequency and amplitude were ranged from 100 to 1200 kHz and from 1 to 100 Vpp, respectively. Test with detection parameters was performed employed a classic univariate approach. Frequency of the 1100 kHz and amplitude of 60 Vpp was found the best condition for separation process. Quantitative analysis was performed in different real samples as well as honey, sausage, biofertilizers, river water, tap water and aquarium environment water. In honey sample found Cl-, NO3- e SO42-. Meia Ponte River and João Leite stream was found Cl- e SO42-. These same species was also found in sausage sample. In the analysis of aquarium environment water was observed Cl-, NO3-, SO42- and NO2-. Besides the quantitative analysis, the monitoring of inorganic ions (Cl-, NO3-, SO42- and NO2-) in aquarium environment with and without fish. The water without fish was possible keep up with nitrification process in the nitrogen cycle and to examine the conversion time of the species involved. On the other hand, in analyses of water with fish the results showed an increase of nitrate concentration over weeks and were possible quatify the nitrite in lethal level for fish. According to the results achieved herein, it is possible to conclude that the use glass electrophoresis chips associated with commercial instrumentation has demonstrated good capability of performing quantitative analysis of important environmental compounds in real samples.